The efficacy of perioperative gabapentin for the treatment of postoperative pain following total knee and hip arthroplasty: a meta-analysis - Kang, Jiayu (J Orthop Surg Res, 2020)
BACKGROUND: Postoperative pain after total knee arthroplasty (TKA) and total hip arthroplasty (THA) influence patients’ rehabilitation and life quality. Although gabapentin has been widely used for analgesia, its efficacy is still controversial in TKA and THA. This meta-analysis was performed to assess the efficacy and safety of gabapentin following TKA and THA. METHOD: Electronic databases including PubMed, EMBASE, Cochrane Central Register of Controlled Trials, MEDLINE, and ClinicalTrials.gov were comprehensively retrieved for randomized controlled trials from their inception to June 2019. A total of 7 studies, which compared the administration of gabapentin with that of placebo for the treatment of postoperative pain, were included in our meta-analysis. The meta-analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. RESULT: There was no difference in pain score at 24 (P = 0.87), 48 (P = 0.15), and 72 (P = 0.85) h associated with the use of gabapentin. Likewise, no difference in accumulative morphine consumption at 48 h following TKA or THA was found between gabapentin and placebo (DM = − 8.14, 95% CI − 18.55 to 2.28, P = 0.13). The incidence of opioid-related adverse effects, including nausea, pruritus, sedation, and dizziness, is no difference between gabapentin and placebo group. However, subgroup analysis indicated that gabapentin could reduce the incidence of pruritus after TKA (RR = 0.35, 95% CI 0.12 to 0.99, P = 0.05). CONCLUSION: Based on our meta-analysis, gabapentin did not decrease postoperative pain, cumulative morphine consumption, and the incidence of adverse effects after TKA and THA. There was not enough evidence to support the administrations of gabapentin for postoperative pain after TKA and THA.